2019
DOI: 10.5937/gp23-23582
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation, humidity and cloudiness in Podgorica (Montenegro) during the period 1951-2018

Abstract: This paper presents the results of a trend analysis of three climate elements: precipitation, cloudiness and humidity. Almost the entire period of instrumental measurements (precipitation and humidity) and visual observations (cloudiness) are covered. In the observed 68-year period , the trend of annual and seasonal precipitation amounts is insignificant. Though, there is a significant decrease in the number of days with precipitation ≥ 1 mm, which implies a movement towards more arid conditions. On the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Burić and Doderović (2019) performed a detailed analysis of precipitation, humidity and cloudiness for Podgorica for the period 1951–2018. Here we will briefly mention some of the results the authors revealed concerning precipitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burić and Doderović (2019) performed a detailed analysis of precipitation, humidity and cloudiness for Podgorica for the period 1951–2018. Here we will briefly mention some of the results the authors revealed concerning precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…Trend of projected annual and seasonal rainfall in Podgorica for the period 2011–2100 according to the RCP8.5 scenario of ALADIN (A), HIRHAM (H) and RACMO (R) models (significantly: * p < .05; + p < .1) Table S1 . Trend of seasonal and annual sums of precipitation and annual precipitation indices, Podgorica 1951–2018 (retrieved from Burić and Doderović, 2019) Table S2 . Differences (°C) in average annual and seasonal temperature projections of ALADIN (A), HIRHAM (H) and RACMO (R) for RCP4.5 and RCP8.5 scenario for Podgorica Table S3 .…”
mentioning
confidence: 99%
“…Observations carried out in Montenegro have demonstrated the absence of ferns in the photic zones of caves [ 5 , 37 ], while in the caves of the Caucasus region, ferns are an obligatory component of the vegetation of the caves entrance zone [ 8 , 39 , 40 ]. This can be associated with higher temperatures, less precipitation in the summer season, and lower humidity in Montenegro, where precipitation rates are decreasing [ 41 ]. No ferns were found in the entrance zones of the caves and grottoes of Gobustan, which confirms the decrease in the number of species that need high humidity in the photic zones of caves in an arid climate.…”
Section: Discussionmentioning
confidence: 99%
“…In the area of the Western Balkans, to which Montenegro belongs, to date any trends in seasonal and annual precipitation have been insignificant over the past 5–6 decades (Filipčić et al ., 2014; Luković et al ., 2014; Burić and Doderović, 2019). However, extreme weather events have become more frequent in Serbia (Malinovic‐Milicevic et al ., 2016; Anđelković et al ., 2018), Croatia (Mihajlović et al ., 2016) and also in Montenegro (Burić et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%